Throughputs of oral hygiene programmes offered at Sefako Makgatho Health Sciences: a retrospective comparison - Mthethwa, SR; Gugushe, TS; Nyalunga, PM (SADJ (Houghton), 2022)
The expansion of the scope of practice of the profession of oral hygiene necessitated the discontinuation of a two-year diploma programme. Aims and objectives To describe and compare the progress to qualification of three cohorts of oral hygiene students enrolled in the diploma and degree programmes at Sefako Makgatho Health Science University. Trends in throughputs were investigated. Design A comparative cross-sectional study. Methods Academic records of three cohorts of first year oral hygiene students enrolled in the diploma and degree programmes were followed up. Data related to the demographic characteristics, numbers enrolled, numbers who dropped out, and the numbers who graduated were acquired and then captured in Microsoft Excel software. Results There was gender parity in enrolment for the diploma programme. Female students constituted the majority of enrolees for the degree programme. The average first year pass rate (83.8% vs 75.8%) as well as average throughput (62.5% vs 56.1%) of the degree programme was higher than that for the diploma programme. Linear trends between cohort size and throughput were not observed. The difference in combined output between the programmes was not statistically significant. Conclusion The average throughput of the degree programme was higher than that for the diploma programme